Left Ventricular Non-Compaction Cardiomyopathy, Ventricular Septal Defect and Pre-excitation: A Rare Coexistence of Three Abnormities in an Adult Patient. - Çınar, Tufan; Çiçek, Vedat; Kılıç, Sahhan; Yalçınkaya, Emre; Selçuk, Murat; Orhan, Ahmet Lütfullah (Nepalese Heart Journal, 2021)
A congenital cardiac condition characterized by ventricular trabeculations and intertrabecular recesses is described as a non-compaction cardiomyopathy. In clinical practice, since it can be associated with severe mortality and morbidity due to progressive heart failure, thromboembolic events, and fatal arrhythmias, it is important to consider non-compaction cardiomyopathy. In this case, we have an adult patient who underwent surgery due to a ventricular septal defect (VSD) and who was later diagnosed with left ventricular non-compaction cardiomyopathy (LVNC) and pre-excitation. To our knowledge, this is the first case of VSD, LVNC, and pre-excitation simultaneously present in an adult patient.